Childhood violence exposure and social deprivation predict adolescent amygdala-orbitofrontal cortex white matter connectivity. (October 2020) - Goetschius, Leigh G.; Hein, Tyler C.; Mitchell, Colter; Lopez-Duran, Nestor L.; McLoyd, Vonnie C.; Brooks-Gunn, Jeanne; McLanahan, Sara S.; Hyde, Luke W.; Monk, Christopher S.
Abstract: Childhood adversity is heterogeneous with potentially distinct dimensions of violence exposure and social deprivation. These dimensions may differentially shape emotion-based neural circuitry, such as amygdala–PFC white matter connectivity. Amygdala–orbitofrontal cortex (OFC) white matter connectivity has been linked to regulation of the amygdala's response to emotional stimuli. Using a preregistered analysis plan, we prospectively examined the effects of childhood exposure to two dimensions of adversity, violence exposure and social deprivation, on the adolescent amygdala–PFC white matter connectivity. We also reproduced the negative correlation between amygdala–PFC white matter connectivity and amygdala activation to threat faces. 183 15−17-year-olds were recruited from the Fragile Families and Child Wellbeing Study — a longitudinal, birth cohort, sample of predominantly low-income youth. Probabilistic tractography revealed that childhood violence exposure and social deprivation interacted to predict the probability of adolescent right hemisphere amygdala–OFC white matter connectivity. High violence exposure with high social deprivation related to less amygdala–OFC white matter connectivity. Violence exposure was not associated with white matter connectivity when social deprivation was at mean or low levels (i.e., relatively socially supportive contexts). Therefore, social deprivation may exacerbate the effects of childhood violence exposure on the development of white matter connections involved in emotion processing and regulation. Conversely, social support may buffer against them.